Thermo-mechanical analysis of a FGM plate subjected to thermal shock - A new numerical approach considering real time temperature dependent material properties - Kaman, Mete Onur; Celik, Nevin; Das, Resul (Walter de Gruyter Gmbh, 2021)
In present the study, sudden cooling, in other words thermal shock, is applied to a plate that is originally a functionally graded material (FGM). The flat plate is assumed to have an edge crack on it. Hence a numerical couple-field analysis is performed on the plate. The FGM is a combination of Ni and Al2O3. The thermal and mechanical properties of the FGM are assumed to depend on temperature variation. The mixing percentages of the Ni and Al2O3 throughout the plate are considered to vary (i) linearly, (ii) quadratically and (iii) in half-order. In order to solve the problem, a new subroutine depending on temperature is written using APDL (ANSYS Parametric Design Language) codes. Three values of the heat transfer coefficient are applied to the initially heated plate. As a result, the transient temperature variation and stress intensity factor are presented to show the thermo-mechanical relation of the plate. The material properties changing with temperature results in more reliable temperature values. Increasing the heat transfer coefficient results in better cooling and in a lesser amount of time to reach ambient air temperature.
Keywords: Functionally graded materials; Stress intensity factor; Thermal shock; Finite element method